A highly-flexible bistable switch based on a suspended monolayer Z-shaped graphene nanoribbon nanoresonator. (February 2020) - Tan, Yi; Xia, Xiao-Shuang; Liao, Xing-Lan; Li, Jian-Bo; Zhong, Hong-Hua; Liang, Shan; Xiao, Si; Liu, Ling-Hong; Luo, Jian-Hua; He, Meng-Dong; Chen, Li-Qun
Abstract: In this work, we theoretically propose a highly-flexible optical bistable switch based on a suspended monolayer Z-shaped graphene nanoribbon nanoresonator (NR). It is shown that bistable nonlinear absorption and refraction response will appear in the strong exciton-NR coupling rme. Specifically, we plot bistability phase diagrams within the system's parameter subspace and derive the critical conditions for optical bistability (OB), which allow one to switch precisely and efficiently OB on/off. The scheme proposed here not only provides a unique platform for measuring the coupling strength between the exciton and the NR, but also may eventually enable applications in the quantum optics and quantum information processing. Graphical abstract: Image 10936